THE EFFECT OF EARNINGS MANAGEMENT, LEVERAGE, AND CAPITAL INTENSITY ON TAX AVOIDANCE - Masrurotus Sholekah; Arisyahidin Arisyahidin; Nisa Mutiara* (Jurnal Apresiasi Ekonomi, 2025)
The study analyzed companies listed in the LQ45 index (IDX) in the 2021-2023 period, and met the research criteria. A total of 84 samples with three periods of financial statements from 28 companies have been received. Using quantitative methods in research, and multiple regression analysis as an analysis tool. The conclusion of this study is that profit management does not affect tax avoidance. Leverage and Capital Intensity affect tax avoidance.